If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y+6.4y(6.4y)=8+5/9
We move all terms to the left:
y+6.4y(6.4y)-(8+5/9)=0
We add all the numbers together, and all the variables
y+6.4y(+6.4y)-(5/9+8)=0
We multiply parentheses
36y^2+y-(5/9+8)=0
We get rid of parentheses
36y^2+y-8-5/9=0
We multiply all the terms by the denominator
36y^2*9+y*9-5-8*9=0
We add all the numbers together, and all the variables
36y^2*9+y*9-77=0
Wy multiply elements
324y^2+9y-77=0
a = 324; b = 9; c = -77;
Δ = b2-4ac
Δ = 92-4·324·(-77)
Δ = 99873
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{99873}=\sqrt{729*137}=\sqrt{729}*\sqrt{137}=27\sqrt{137}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-27\sqrt{137}}{2*324}=\frac{-9-27\sqrt{137}}{648} $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+27\sqrt{137}}{2*324}=\frac{-9+27\sqrt{137}}{648} $
| 18+19z=-2+17z | | (3x-1)÷2=(5x+2)÷3+1 | | 3x-5(x-4)=-7+5x-15 | | (3x-1)÷2=(5x+2)÷2+1 | | 47-9x=13+8x | | 22/x=21/3 | | 6/7+7m/3=74/24 | | 2k+4=24 | | -8(-4+6x)=32+3x | | -18n+3=-8-3n-16n | | 5+b/7=1.7 | | 5/3x+7-7=2x-2 | | 4(×+10)=50+2x | | 2x+2=3x=63 | | 7-5v=-6v+2v | | x/20+6=5 | | 5y^2-8y-3=0 | | 21/4x+9/8=2 | | 10x-8=4-8 | | 6b+6=1+7b | | 7+3y=6+2y-5+y | | X-4/x-5=5/4 | | -5y^2-8y-3=0 | | (6x-2)+(3x+6)+2x=180 | | x+45=540 | | 1/3y-5=1/2y | | 4(2b^2-b-45)=0 | | 12=10x12 | | t-(-32)=5 | | 4-6q=8q+18 | | 2(n+2)=5n+1-2n | | 9-2+3y=6+2y-5+y |